PERAN MEDIA GAME EDUKASI WORDWALL DALAM PEMBELAJARAN MODEL DISCOVERY LEARNING PERUBAHAN WUJUD BENDA SISWA SEKOLAH DASAR - Fauziyah, Risa; Achmad Fanani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is in the background because of the lack of student activity in learning activities and is a problem in the learning process in the classroom because students are an important indicator in the effective learning process. This is because teachers tend to use conventional methods and lack in utilizing learning media. The purpose of this study is to increase the activeness and understanding of the material of the Change of Form of Elementary School students in the learning process. This study uses a type of quantitative research with a "quasi-experimental design" design in the form of a posttest only control group design. The research was conducted in one of the elementary schools with the research subject of grade IV students who studied material on changes in the form of objects. The subjects of this study consisted of 25 students from grades IV-A and IV-B at SDN Kepuh Kiriman 1 Waru. The data collection technique uses Posttest Only and the average test scores of the Experiment class and the Control class have differences. The Experiment class had an average test score of 71.84, while the Control class had an average test score of 50.56. This can be proven by the results of hypothesis testing using an independent Sample T-test which shows a sig value. ( 2 – tailed) 0.000. Which shows that wordwoll educational game media in Discovery Learning has a very influential role in the activeness and understanding of material changes in the form of elementary school students in the Learning Process.